Chronic Scaphoid Nonunion of 28-Year Duration Treated with Nonvascularized Iliac Crest Bone Graft - Capo, John T.; Shamian, Ben; Rivero, Steve (Journal of Wrist Surgery, 2013)
Scaphoid nonunions present a challenging clinical problem, particularly if the diagnosis of nonunion is missed or delayed. The optimal management technique can vary from free vascularized bone grafts to scaphoid excision and limited wrist fusion. The classic method of open reduction, nonvascularized corticocancellous bone grafting and internal fixation is still an effective technique. In this report, we describe a case of a 28-year-old chronic scaphoid nonunion treated with nonvascular iliac crest bone graft and internal fixation.
Keywords: scaphoid nonunion; chronic; bone graft; iliac crest